Integrated IOT and voice-controlled home automation system / Ariel Lihan Robert - Robert, Ariel Lihan (2024)
Advancement in smart home technology involves the use of voice recognition devices to control all home appliances, becoming a trend. The integration of Internet of Things (IoT) technology and voice-controlled home automation systems has revolutionized our interaction with homes. Many individuals wish for their homes to be equipped with IoT and voice-controlled technology, maximizing efficiency in tasks such as controlling appliances effortlessly while on the couch and improving home security. Currently, IoT is an active research area for security, comfort, and reliability, widely used to control appliances remotely. This study proposes voice-controlled house appliances and IoT monitoring capability. The aim of the study is twofold. First, to create a home automation system using Arduino and a voice recognition microphone to detect and convert voice commands into specific actions. Second, to develop a user-friendly model of a home automation device, allowing manual customization of voice commands for specific actions. This system aims to make households more reliable, marketable, and comfortable.